2007
DOI: 10.1523/jneurosci.4652-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Determines Membrane Potential Dynamics and Controls Action Potential Generation in Awake and Sleeping Cat Cortex

Abstract: Intracellular recordings of cortical neurons in awake cat and monkey show a depolarized state, sustained firing, and intense subthreshold synaptic activity. It is not known what conductance dynamics underlie such activity and how neurons process information in such highly stochastic states. Here, we combine intracellular recordings in awake and naturally sleeping cats with computational models to investigate subthreshold dynamics of conductances and how conductance dynamics determine spiking activity. We show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
249
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(293 citation statements)
references
References 36 publications
40
249
3
1
Order By: Relevance
“…This simulation (Fig. 4, Awake), allows us to verify that these conductance measurements led the model to generate V m activity in excellent agreement with the intracellular recordings (see details in Rudolph et al, 2007). Similarly, integrating conductance measurements during up-states (not shown) generated V m activity consistent with the up-down-state transitions seen experimentally (Fig.…”
Section: Single-cell Model Of Activated Statessupporting
confidence: 74%
See 2 more Smart Citations
“…This simulation (Fig. 4, Awake), allows us to verify that these conductance measurements led the model to generate V m activity in excellent agreement with the intracellular recordings (see details in Rudolph et al, 2007). Similarly, integrating conductance measurements during up-states (not shown) generated V m activity consistent with the up-down-state transitions seen experimentally (Fig.…”
Section: Single-cell Model Of Activated Statessupporting
confidence: 74%
“…These features were confirmed recently by relating those conductance measurements to a spike-triggered average (STA) conductance analysis Rudolph et al, 2007;Piwkowska et al, in press). It was found that the main synaptic conductance pattern associated to spikes in cortical neurons was a decrease of total conductance, which was due to a decrease of inhibitory conductance (Fig.…”
Section: Experimental Characterization Of Activated Cortical Statesmentioning
confidence: 54%
See 1 more Smart Citation
“…The repeated inhibitory conductance led to a higher precision than the repeated excitatory conductance. To find out what type of input most effectively drives the cell in vivo, a reverse correlation analysis 113 was performed on the inhibitory and excitatory conductance waveforms separately 114 . This showed that spikes of neurons in the association cortex of the cat were on average preceded by a reduction in inhibition.…”
Section: Inhibition Can Modulate Firing Rate and Influence Spike Timesmentioning
confidence: 99%
“…These tests confirmed the weakness of the method in the low-inhibition regime, but also revealed a good performance of the VmT method during HC states. Since in cortical neurons in vivo the membrane potential is usually well above the inhibitory reversal potential, and since inhibitory conductances tend to dominate over excitatory ones (Borg-Graham et al, 1998;Rudolph et al, 2007; note that dendritic recordings may be dominated by excitatory inputs), we anticipate that this method should provide good conductance estimates from in vivo recordings. Gaussian white noise was added to the voltage trace of the model, and the VmT method was applied to the V m trace obtained with noise, to yield estimates of conductances and variances.…”
Section: Discussionmentioning
confidence: 99%